Դեկորատիվ-կիրառական արվեստի դերը ազգային ավանդույթների ձևագոյացման ընթացքում - Եղիազարյան, Անուշ
Medieval Armenian culture was one of the profound pages of international culture. In contrast with architectural and bookish landscape, the decorative art of Medieval Armenia wasn't in the center of much study. Only some separate works of art or manuscripts were being noticed by the explorers. However, the existing samples testify the fact that those branches of decorative art which are closely related to architecture (applied art, decorative things for everyday use) are of unique quality. It's necessary to mention that formation of national traditions, turning to the classical solutions were considered to be a unique school for medieval decorative art, for the painters and architectures of any new generation.
Keywords: Մշակույթ; Դեկորատիվ-կիրառական արվեստ